Introduction to SharePoint 2010 - Connors, Lisa.; Safari eBooks ([S.l.] : CompuWorks, 2012)
"This course is designed for the user who has been assigned contribute permissions to a SharePoint Foundation Team web site and needs to learn how to navigate and add content to the site. This course assumes you are familiar with personal computers and have experience using Windows 7. During this course, you'll learn how to navigate, create and contribute content to a Team web site, set permissions and understand lists and libraries. This course also demonstrates the integration of SharePoint with Microsoft Office 2010."--Resource description page.
Title from title screen.
Publication information from resource description page (viewed Apr. 8, 2013).
Presenter, Lisa Connors.
Keywords: Intranets (Computer networks); Microsoft SharePoint (Electronic resource); Web servers; Electronic books